PENGARUH UKURAN PERUSAHAAN (FIRM SIZE) DAN PROFITABILITAS PERUSAHAAN (PROFITABILITY) TERHADAP STRUKTUR MODAL (CAPITAL STRUCTURE) - Yanti Andriani, Neneng (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2023)
This research was conducted on 12 manufacturing companies listed on the Indonesia Stock Exchange for the period 2018-2021. This study aims to determine the effect of company size and profitability on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange for the period 2018-2021. The design in this study used this research using the ex-post facto method. The population in this study were 12 manufacturing companies listed on the Stock Exchange with a non-probability sampling technique using a saturated sample technique. The data used is secondary data, namely financial statements for the 2018-2021 period. Statistical analysis and relationship analysis methods used Pearson correlation analysis, coefficient of determination, multiple linear regression and to test the hypothesis used t test and F test. The results of the research that has been done can be seen that firm size and profitability have a linear relationship with capital structure, with the criteria of the relationship very strong with an R value of 0.909. Likewise, the results of multiple linear regression analysis show a positive and unidirectional relationship which is expressed by the equation Y = 0.709 + 0.035X1 + 0.625X2. From the analysis of the coefficient of determination (R2) shows that the magnitude of the effect of Firm Size and Profitability on Capital Structure is 82.6%, the remaining 17.4% is influenced by other variables not examined. The results of the significance test simultaneously show that Firm Size and Profitability have a value of sig < 0.05 (0.000 < 0.05) and has a calculated F value > F table that is 21.419 > 4.103, so it can be concluded that the hypothesis proposed can be accepted that the Company and Profitability together have a significant effect on the Capital Structure.